Launching a business consultancy in the financial sector - Ng, Jimmy Hwee Kim (2009)
Business consultancy, a Western concept, is a growth industry in Asia where it has only recently begun to gain acceptance. Faced with globalisation and changing skill requirements, Asian companies are beginning to overcome their traditional suspicions and hiring business consultants. Jumping on this trend, Western consultants have been scrambling for Asian business and adapting their services to the Asian environment.